THE ROLE OF PREPOSITIONS IN ENGLISH LANGUAGE INSTRUCTION TO YOUNG LEARNERS - Nuratdinova, N.B. (SCIENCE and SOCIETY, 2025)
This article explores the importance of teaching prepositions to young learners in English language instruction. The study examines the challenges young learners face in mastering prepositions and discusses effective pedagogical approaches to overcome these challenges. By reviewing relevant literature and analyzing classroom practices, the paper highlights the critical role prepositions play in enhancing learners' communicative abilities.